Siri dan al-Ḥayāʾ: Membumikan Etika Al-Qur'an melalui Kearifan Lokal dalam Tafsir al-Munīr Karya Daud Ismail - Muhammad Agus; Hamzah; Ahmad Syauqu Habibie (Al Furqan: Jurnal Ilmu Al Quran dan Tafsir, 2026)
The relationship between local wisdom and Qur'anic ethics has become an important theme in contemporary Qur'anic studies, particularly within the tradition of Indonesian vernacular exegesis. This study examines how the Bugis concept of siri is represented in Tafsir al-Munīr by Daud Ismail and investigates its relationship with the Qur'anic ethical principle of al-ḥayāʾ (modesty and moral shame). The research is motivated by the contemporary distortion of siri within Bugis society, where a value originally intended to preserve human dignity is frequently reduced to a justification for violence and honor-based retaliation. Employing a qualitative library research design, this study applies the Conceptual Framework of Indonesian Qur'anic Exegesis, which analyzes the work through its ontological foundation, language and script, presentation, methodology, and exegetical characteristics. The findings demonstrate that Daud Ismail does not explicitly discuss siri as an independent interpretive theme, nor does he directly associate his exegesis with Bugis cultural philosophy. Nevertheless, the ethical substance of siri is implicitly embedded through the vernacularization of Qur'anic moral concepts into the local Bugis language. Rather than merely preserving a cultural tradition, Tafsir al-Munīr establishes a dialogical relationship between local values and Qur'anic ethics, in which siri provides social and cultural relevance while the Qur'an offers normative ethical guidance and theological boundaries. Consequently, siri is reconstructed from a collective cultural norm into a universal ethical value grounded in Qur'anic teachings, emphasizing dignity, moral responsibility, humility, and humanistic principles. This study contributes to the growing scholarship on vernacular Qur'anic exegesis by demonstrating how local cultural concepts can be critically integrated into Islamic ethical discourse without compromising the normative authority of the Qur'an.